Targeting Hsp20 Using the Novel Small Non-coding RNA DnrH Regulates Heat Tolerance in Deinococcus radiodurans - Xue, Dong; Chen, Yun; Li, Jiang; Han, Jiahui; Liu, Yingying; Jiang, Shijie; Zhou, Zhengfu; Zhang, Wei; Chen, Ming; Lin, Min; Ongena, Marc; Wang, Jin (Frontiers in Microbiology, 2019)
Small noncoding RNAs (ncRNAs) are a class of regulatory molecules, which remain understudied in bacteria. In the extremophilic bacterium Deinococcus radiodurans, although hundreds of ncRNAs have been identified, few have been characterized in detail. In this study, we report the identification and characterization of a novel heat-inducible ncRNA named DnrH. Heat tolerance analysis showed that deleting DnrH significantly inhibited viability in response to high temperature conditions. Comparative phenotypic and qRT-PCR analyses of a DnrH mutant (∆DnrH) and wild-type (WT) D. radiodurans suggested that DnrH is potentially involved in regulating the expression of the heat shock-related gene Hsp20. Microscale thermophoresis and genetic complementation showed that a 28-nucleotide (nt) sequence in the stem-loop structure of DnrH (143–170 nt) pairs with its counterpart in the coding region of Hsp20 mRNA (91–117 nt) via a 22 nt region. In vivo, mutation of the 22-nt region in the D. radiodurans genome led to a reduction in heat tolerance similar to that observed in the DnrH-mutant. Our results show that DnrH positively influences heat tolerance by increasing the transcription of Hsp20 mRNA, demonstrating, for the first time, a ncRNA that directly controls the expression of a heat stress-resistance gene. This work provides new insight into the heat stress response mechanism of D. radiodurans as well as other extremophiles that express similar Hsp20 proteins.